1995
DOI: 10.2134/agronj1995.00021962008700060023x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Alfalfa and Berseem Clover for Forage and Plowdown Nitrogen in Barley Rotations

Abstract: Annual legume plowdown systems, which utilize fall regrowth for N contributions to rotational crops, have not been adapted to irrigated, intermountain areas of the Northern Rockies. Our objective was to evaluate plowdown systems using ‘Nitro’ alfalfa (Medicago sativa L.) and ‘Bigbee’ berseem clover (Trifolium alexandrinum L.). These two legumes were grown under five harvest management systems (zero to three forage harvests prior to fall plowdown of regrowth, or a standard three harvest system with no herbage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Similarly, Westcott et al (1995) concluded that green manure effects on subsequent spring soil nitrate levels were a determining factor in barley N uptake and yield responses to treatments.…”
Section: Impact On Subsequent Barleymentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Westcott et al (1995) concluded that green manure effects on subsequent spring soil nitrate levels were a determining factor in barley N uptake and yield responses to treatments.…”
Section: Impact On Subsequent Barleymentioning
confidence: 99%
“…Net N mineralization has been shown to correlate with C:N ratios of clover green manures . In a study comparing plough-down of berseem clover and alfalfa (Medicago sativa L.), soil N availability was consistently greater for alfalfa, although above-ground biomass N was higher for berseem clover than alfalfa (Westcott et al 1995). It was suggested that the higher soil N availability with alfalfa may have been due to greater N contributions from roots and crowns.…”
Section: Impact On Soil Nitratementioning
confidence: 99%
See 3 more Smart Citations